The Mekong delta transport infrastructure development project = (The World Bank in Vietnam (WB), 2006)
The development objective of the project is to improve access to markets by businesses, farmers and the poor with lower logistics costs resulting from the alleviation of key physical and institutional bottlenecks of the main transport corridors in the Mekong Delta region. The Project will have four main components: 1) Component A, National Road Corridors, aims to improve the standard of national trunk roads connecting the main economic hub of the Mekong Delta; 2) Component B, National Waterway Corridors, aims to improve the standard of trunk waterways connecting the Northern and Coastal Delta areas to Can Tho and HCMC; 3) Component C, Connecting the Poor to the Supply Corridors will improve the feeder waterways, roads, ports, and landing stages at the district and provincial levels to link poorer and more distant producer communities to the main supply corridors; and Component D, Institutional Support to Ministry of Transport will provide consultancy services on multi-modal transport, institutional support to the Vietnam Inland Waterways Administration, training and project implementation support.